P5-S4.04 The interface between HPV vaccine implementation and STI prevention: HPV vaccine discussions as an opportunity to provide messages about sexual health. (10th July 2011) - Gottlieb, S; McRee, A L; Reiter, P; Dittus, P; Halpern, C; Brewer, N
Abstract : Background: Early parent–child communication about sex is associated with healthier behaviour during adolescence. Understanding parents' cues to initiating these conversations may provide new opportunities for public health intervention. Human papillomavirus (HPV) vaccine is recommended for all 11–12-year-old girls and is highly acceptable to parents. We sought to characterise mothers' communication with their daughters about HPV vaccine and the potential for HPV vaccine discussions to provide an opportunity for discussions about sex. Methods: During December 2009, we conducted an online survey with a nationally representative sample (n=900) of US mothers of adolescent females aged 11–14 years (response rate=66%). We compared the proportion of all mothers using HPV vaccine discussions as a cue to talking about sex vs other potential cues using McNemar's χ 2 . We also assessed whether communication about HPV vaccine was independently associated with communication about sex using multivariate logistic regression. Estimates are weighted. Results: Sixty-five per cent of mothers reported talking with their daughters about HPV vaccine, of whom 41% said that doing so led to a conversation about sex. Thus, 27% of all mothers talked about sex as a result of HPV vaccine conversations, similar to the proportion talking about sex as a result of some more widely recognised cues, such as their daughter starting menses (21%) or talking about alcohol or drugs (29%), but less than some others, such as their daughters showing an interest in boys (36%; p<0.05) or having sex education at school (46%; p<0.05). Mothers who had talked with their daughters about HPV vaccine were more likely than those who had not to have ever talked with their daughters about sex (92% vs 74%, p<0.001), even after controlling for other cues and factors associated with communication about sex (OR=3.1, 95% CI 1.4 to 6.5). Among mothers who talked about sex when talking about HPV vaccine, many felt HPV vaccine provided a good reason to do so (64%) or that it made it easier to start a conversation (33%). Conclusions: HPV vaccine discussions provide an acceptable opportunity for mothers to talk with their daughters about sex at an age when such communication is most influential. It may be possible to capitalise on HPV vaccine discussions to promote parent–child communication about sex and provide messages about sexual health and STI prevention to early adolescents.